11. "Seeing Is Believing": The Importance of Visual Factors in Music Performance Assessment - Iușcă Dorina Geta (Sciendo, 2020)
The criteria recommended for the performance of internal assessment are the ones included in the national model for school inspection applied by the inspectors in the school inspectorate or the Ministry of Education (with subsequent names) who carry out internal assessments. Educational establishments can also decide on certain additional criteria - in line with the specific needs. All educational establishments must perform the annual assessment of activity, regarding school development, educational programs, curricular and extracurricular activities, quality of the teaching-learning process, human resources development, relations with the community and European dimension in the education offered. A tricky problem is represented by the specific assessment of Children Centres and Clubs that carry out non-formal activity, without school programs and handbooks approved by the Ministry of Education. Carrying out an analysis of the manner of assessing formal and non-formal educational units, the need to readjust the internal and external assessment was identified. At the level of school inspectorates, school inspection is carried out by a team consisting of specialised inspectors who know the specificity of those educational units. The main problem is represented by the external assessment carried out by ARACIP with the help of standard specific means: fields, indicators, reference descriptors and specific descriptors. Through the study performed, a series of proposals on the beneficial amendments for the quality assessment within Children Centres and Clubs is identified.